Synthesis and Pharmacological Evaluation of Fluorinated Quinoxaline‐Based κ‐Opioid Receptor (KOR) Agonists Designed for PET Studies. (1st September 2020) - Tangherlini, Giovanni; Börgel, Frederik; Schepmann, Dirk; Slocum, Samuel; Che, Tao; Wagner, Stefan; Schwegmann, Katrin; Hermann, Sven; Mykicki, Nadine; Loser, Karin; Wünsch, Bernhard
Abstract: κ‐Opioid receptors (KORs) play a predominant role in pain alleviation, itching skin diseases, depression and neurodegenerative disorders such as multiple sclerosis. Therefore, imaging of KOR by a fluorinated PET tracer was envisaged. Two strategies were followed to introduce a F atom into the very potent class of cis, trans‐configured perhydroquinoxalines. Whereas the synthesis of fluoroethyltriazole 2 has already been reported, fluoropyrrolidines 14 (1‐[2‐(3, 4‐dichlorophenyl)acetyl]‐8‐[(R)‐3‐fluoropyrrolidin‐1‐yl]‐perhydroquinoxalines) were prepared by SN 2 substitution of a cyclic sulfuric acid derivative with hydroxypyrrolidine and subsequent transformation of the OH moiety into a F substituent. Fluoropyrrolidines 14 showed similar low‐nanomolar KOR affinity and selectivity to the corresponding pyrrolidines, but the corresponding alcohols were slightly less active. In the cAMP and β‐arrestin assay, 14b (proton at the 4‐position) exhibited similar KOR agonistic activity as U‐50, 488. The fluoro derivatives 14b and 14c (CO2 CH3 at the 4‐position) revealed KOR‐mediated anti‐inflammatory activity as CD11c and the IFN‐γ production were reduced significantly in mouse and human dendritic cells. Compounds 14b and 14‐c also displayed anti‐inflammatory and immunomodulatory activity in mouse and human T cells. The PET tracer [ 18 F]‐2 was prepared by 1, 3‐dipolar cycloaddition. In vivo, [ 18 F]‐2 did not label KOR due to very fast elimination kinetics. Nucleophilic substitution of a mesylate precursor provided [ 18 F]‐14c . Unfortunately, defluorination of [ 18 F]‐14c occurred in vivo, which was analyzed in detail by in vitro studies. Abstract : κ‐Opioid receptors (KORs) play a prominent role in pain alleviation, skin diseases, depression and neurodegenerative disorders. Two strategies were pursued to prepare fluorinated tracers for positron emission tomography based on the perhydroquinoxaline class of KOR agonists. The agonists showed high KOR affinity, selectivity, agonistic activity and KOR‐mediated anti‐inflammatory and immunomodulatory activity. One tracer was quickly eliminated, another was defluorinated.